PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS POWER POINT (MACRO-ENABLED) PADA MATA KULIAH GEOMETRI EUCLID DALAM PEMBELAJARAN MATEMATIKA - Nursit, Isbadar (Media Pendidikan Matematika, 2016)
This development research aims is to develop an interactive of mathematics learning media using Visual Basic for Application based on Ms. program. Power Point. The development of this medium was using 4D development model, namely: (D) efine, (D) esign, (D) evelop, (D) issiminate, and the resulting product in the form of learning media on Euclid geometry subject. Based on the trial of product, the material expert stated that the product is valid with the validity percentage of 82.5%, the media expert stated that the product is valid with the validity percentage of 83.4%, and the practitioner stated that the product is valid with the validity percentage of 86% and the user / user stated the product practically with the percentage of practicality is 84%. Thus, it can be concluded that the resulting product is valid and the product can be applied in the classroom as well as beneficial for the students.